Social Work Research Using Arts-Based Methods - Huss, Ephrat (Book collections on Project MUSE., 2022)
In the first dedicated analysis of its kind, international experts review the rationale and results of arts-based approaches to research, teaching, and practice in social work. The book presents examples of their use and methods to evaluate and theorise results and shows how arts can form outputs from research too.